2016
DOI: 10.9734/arrb/2016/29928
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Groups and Malaria Parasitaemia in Outpatients of BMSH Port Harcourt, Rivers State

Abstract: A cross -sectional study was conducted to investigate the relationship between ABO blood groups and malaria parasitaemia in Port Harcourt, Rivers State, Nigeria. Thick and thin films made from venous blood samples collected from 1000 consenting outpatient study subjects, were stained with 10% Giemsa stains and viewed microscopically using oil immersion objective to detect malaria parasites following standard parasitological techniques. ABO blood group typing with monoclonal Antisera A, B and D was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, the number was higher than that of previous reports in other parts of the State. Wogu and Nduka (2016) and Wogu et al (2017) recorded a prevalence of 32% and 43.1%, respectively in Port Harcourt. However, the observed prevalence in different study areas in the State was lower than the numbers reported by Wokem et al (2017) and Augustine-D' Israel and Abah (2018), which were 87% and 78%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the number was higher than that of previous reports in other parts of the State. Wogu and Nduka (2016) and Wogu et al (2017) recorded a prevalence of 32% and 43.1%, respectively in Port Harcourt. However, the observed prevalence in different study areas in the State was lower than the numbers reported by Wokem et al (2017) and Augustine-D' Israel and Abah (2018), which were 87% and 78%, respectively.…”
Section: Discussionmentioning
confidence: 96%